A Bibliometric Analysis of Entrepreneurial Intentions among International Students - Andrea Gubik; Hüseyin Ozan Altýn (Management)
Research Question: What is the contemporary academic literature on the entrepreneurial intentions of international students? What are the theories, modern approaches and research patterns in this field? Motivation: Although entrepreneurial intention – one of the best indicators for entrepreneurial activity – is a well-researched concept, the entrepreneurial intentions of international students have only recently started receiving attention. This is due to a significant increase in the proportion of international students in recent years. Understanding the entrepreneurial intentions of international students can provide valuable insights to policy-makers and practitioners in fostering entrepreneurship opportunities. Therefore, examining and highlighting the academic literature surrounding the field may facilitate future studies, which in turn can lead to more effective policies regarding international students' entrepreneurial issues. Data: Forty studies were identified and retrieved from different academic databases: EBSCO, Google Scholar, Scopus and Web of Science, with the keywords “international student” and “entrepreneurial intention”. Specific information on each study was extracted and further utilised for the analysis, such as author information, publication year, location, research methods and research themes. Tools: A bibliometric analysis was carried out, from which we learned the most important quantitative characteristics, and then we supplemented this with descriptive and evaluative analyses. Findings: Although the number of studies from the research indicates an academic gap, the increasing number of publications from recent years shows that scholarly interest in this field is growing. All studies on this topic were published after 2010. The research has revealed that the studies are diverse in terms of scope, discipline and methodology. Entrepreneurial education is the most often researched field, followed by gender issues, self-efficacy, and the other components of the Theory of Planned Behaviour, such as attitudes, subjective norms and perceived behaviour control. Overall, there are no differences between international and national research fields based on the nature of the variables included in the studies. Contribution: The paper provides a bibliometric analysis of publications dealing with international students' entrepreneurial intentions. It outlines the current research patterns and outcomes and identifies areas that require further research. The paper highlights the need for research into contextual issues such as the role of cultural and other differences between the home and host countries.